Workplace Stress and Coping Mechanisms: A Study of Occupational Health Psychology in Thailand - อุดเมืองเพีย, สุรศักดิ์ (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2024)
Workplace stress is a pressing issue in Thailand, significantly influencing occupational health and organizational productivity. This study investigates the causes, impacts, and coping mechanisms associated with workplace stress within the unique socio-cultural and economic context of Thailand. Using frameworks from occupational health psychology, it explores how job demands, cultural norms, and organizational culture exacerbate stress levels. The findings highlight the psychological and physical repercussions of stress, including anxiety, burnout, and reduced productivity, as well as the role of coping strategies such as problem-focused and emotion-focused approaches. Emphasizing the need for culturally sensitive interventions, the study underscores the importance of supportive organizational cultures and effective stress management programs. This research contributes to the growing body of knowledge on occupational health psychology, offering actionable insights for enhancing employee well-being and organizational outcomes in Thailand.